HISTORICAL STAGES OF FORMATION OF THE DESIGN OF REHABILITATION CENTERS FOR THE MILITARY - ЗАСТАВНИЙ, Р. С. (Art and Design, 2024)
Purpose: Based on a retrospective analysis of the development of the design of rehabilitation centers for the military, identify the key stages and factors that influenced its development. The article applies a comprehensive approach to the analysis of the design of rehabilitation centers for the military, including a historical review based on archival materials and scientific publications, an analysis of technological, ergonomic, medical and socio-cultural aspects. The results of the study showed that the evolution of the design of rehabilitation centers for the military has gone through several key stages since the First World War. During this period, the spaces were mostly functional, focused on physical rehabilitation, often in limited conditions. During the Second World War, attention to spatial solutions that ensured comfort increased, but the problem of insufficient privacy for patients remained in the institutions of that time. In the post-war period, there was a trend towards a more balanced approach that combined functionality with comfort and psychological support. Although the design became more open and technologically advanced, there was still a need to individualize the space and ensure privacy for more effective recovery. For the first time, a systematic analysis of the historiography of the design of rehabilitation centers was carried out, taking into account technological, ergonomic, medical and socio- cultural factors. Practical significance of the study emphasizes the need to create comfortable and functional rehabilitation spaces for veterans. The growing number of patients requires new architectural and design solutions that meet modern standards and needs. The results of the analysis of historical stages of design allow to create more efficient and comfortable spaces that increase the quality of rehabilitation and life of veterans.